Non-alcoholic steatohepatitis animal model induction - Abdul Rahim, Roslina; Abdul Ghani, Azril Shahreez; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Ramli, Norazsida (World Journal of Pharmacy and Pharmaceutical Sciences (WJPSS), 2019)
Aim: The aims of this study are to establish NASH animal model utilizing 1% and 12% cholesterol diet. Methods: This study begins with the induction phase with cholesterol diet. In the induction phase, 42 Sprague-Dawley rats were randomly divided into standard diet (std) group (n=12) and NASH group (n=30). The 12 rats in the std group were fed with commercial rat pellet while the 30 rats in the NASH group were fed with 1% cholesterol (1% CD) diet for 14 weeks. The experiment was extended for an additional 6 weeks with increment of cholesterol in the diet from 1% to 12 % in the NASH group since the liver histology did not show features of NASH in the 1% CD. Results: At the end of the additional 6 weeks period, liver histology showed NASH changes in the 12% CD. Results of the histological sections of the livers of the 12% CD rats in the induction phase exhibited features consistent with NASH which include macrovesicular steatosis, occasional hepatocyte ballooning degeneration with mild to moderate lobular and portal inflammation. The 12% CD group revealed significantly increased serum alanine aminotransferase (ALT), serum insulin levels, homeostatic model assessment insulin resistance (HOMA-IR), serum total cholesterol (TC), serum low-density lipoprotein cholesterol (LDL-c) and reduced high-density lipoprotein cholesterol (HDL-c) in rats. Conclusion: This study has successfully induced mild–moderate NASH rat model utilizing 12% cholesterol diet.